Determining AI-Based Learning Adoption Model for Students in Entrepreneurship Education: A Design Thinking Approach - Cep Abdul Baasith Wahpiyudin; Sabda Alam Muhammadan; Riska Amalia; Adelia Chrisanta; Asep Taryana (Journal of Consumer Sciences)
Background: Student interest in entrepreneurial pursuits remains low, despite the significant contributions of entrepreneurship to economic growth.